2016
DOI: 10.1523/jneurosci.3150-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Cornu Ammonis Area 1 Theta-Nested Gamma Oscillations Induced by Optogenetic Theta Frequency Stimulation

Abstract: Gamma oscillations (30 -120 Hz) are thought to be important for various cognitive functions, including perception and working memory, and disruption of these oscillations has been implicated in brain disorders, such as schizophrenia and Alzheimer's disease. The cornu ammonis area 1 (CA1) of the hippocampus receives gamma frequency inputs from upstream regions (cornu ammonis area 3 and medial entorhinal cortex) and generates itself a faster gamma oscillation. The exact nature and origin of the intrinsic CA1 gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
108
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(141 citation statements)
references
References 34 publications
33
108
0
Order By: Relevance
“…Recently, Schomburg et al (2014) showed that local hippocampal theta–gamma coupling at 30–60 Hz is more prominent at the proximal CA1, where GABAergic interneurons are strongly driven by Schaffer collaterals (Oliva et al, 2016). Both in epileptic and control rats, slow gamma oscillations were in phase with CSD sinks at the SR, which is consistent with this feedforward activation model (Mann et al, 2005; Zemankovics et al, 2013; Butler et al, 2016). PV basket cell firing at the falling theta phase have been involved in the mechanism (Lasztóczi and Klausberger, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, Schomburg et al (2014) showed that local hippocampal theta–gamma coupling at 30–60 Hz is more prominent at the proximal CA1, where GABAergic interneurons are strongly driven by Schaffer collaterals (Oliva et al, 2016). Both in epileptic and control rats, slow gamma oscillations were in phase with CSD sinks at the SR, which is consistent with this feedforward activation model (Mann et al, 2005; Zemankovics et al, 2013; Butler et al, 2016). PV basket cell firing at the falling theta phase have been involved in the mechanism (Lasztóczi and Klausberger, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…An intrahippocampal slow gamma generator (30–60 Hz) operates at the falling phase of theta coincident with CA3 Schaffer inputs arriving at the stratum radiatum (SR; Csicsvari et al, 2003; Lasztóczi and Klausberger, 2014). A third, even faster, generator (>100 Hz) runs locally at SP during the negative peak of theta when CA1 pyramidal cells (PCs) fire maximally (Schomburg et al, 2014; Butler et al, 2016). A detailed proximodistal arrangement along the hippocampal axis from CA3 to subiculum implements entorhinal–hippocampal function (Henriksen et al, 2010; Bellistri et al, 2013; Schomburg et al, 2014; Laurent et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…in the theta frequency range), these slices expressed a nested gamma‐frequency oscillation at about 45 Hz (Fig. , Butler et al ., ; Akam et al ., ; Pastoll et al ., ). Similar to our previous findings with pharmacologically induced gamma oscillations, the properties of optogenetically induced gamma oscillations did not change in the presence of 100 n m TGOT [Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Typical firing rates of FSI in their in vitro model were below 1 Hz during baseline conditions and reached 8 Hz in presence of TGOT. In vitro models of gamma‐frequency oscillations typically produce firing rates of FSI around 30–45 Hz (Bartos et al ., ; Butler et al ., ), and SPW‐R oscillations in vitro go along with firing rates around 6 Hz (Bähner et al ., ). Thus, OT can have a strong impact on firing frequency during SPW‐R oscillations while the high‐frequency firing of FSI during gamma activity may limit the range for additional enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of septal fast‐spiking GABAergic neurons is also linked to the induction of high‐frequency gamma oscillations (30–100 Hz; Buzsaki & Wang, ). Both slow theta and fast gamma hippocampal oscillations depend on the burst discharges of septal interneurons, but hippocampal theta and gamma are also mediated by the activity of entorhinal inputs (Pernia‐Andrade & Jonas, ) and local rhythm generators (Goutagny et al ., ; Butler et al ., ). One hypothesis is that hippocampal self‐generated theta generators (Kocsis et al ., ; Goutagny et al ., ; Stark et al ., ) can resonate or interfere with the septum‐generated theta oscillation, which in turn could amplify or reduce the limbic theta waves (Patel et al ., ).…”
Section: Septal Theta Rhythm Generationmentioning
confidence: 99%